2017
DOI: 10.4265/bio.22.67
|View full text |Cite
|
Sign up to set email alerts
|

Biopreservative Efficacy of Bacteriocin BacFL31 in Raw Ground Turkey Meat in terms of Microbiological, Physicochemical, and Sensory Qualities

Abstract: The effect of the semi purified bacteriocin BacFL31 at 200 and 400 AU/g on the shelf life of refrigerated raw ground turkey meat was investigated. The microbiological, physicochemical, and sensory properties of the meat samples were examined during refrigerated storage. The findings indicated that BacFL31 treatments were effective p<0.05 against the proliferation of various spoilage microorganisms and suppressed the growth of Listeria monocytogenes and Salmonella Typhimurium. The pH, % Met-MB, and TBA-RS value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Similarly, the purified bacteriocin was successful in containing the growth of L. monocytogenes up to 7 th day as compared to control inoculated with L. monocytogenes which is even better than with the results achieved with chemical preservative. These findings are in agreement with the few results currently available in the literature, including the work of (Chakchouk-Mtibaa et al, 2017), where the effect of the semi purified bacteriocin BacFL31 was investigated on the shelf life of refrigerated raw ground turkey meat. The findings indicated that BacFL31 treatments were effective against Listeria monocytogenes and Salmonella Typhimurium.…”
Section: Comparison Of Preservative Potential Of Bacteriocin With Chesupporting
confidence: 92%
“…Similarly, the purified bacteriocin was successful in containing the growth of L. monocytogenes up to 7 th day as compared to control inoculated with L. monocytogenes which is even better than with the results achieved with chemical preservative. These findings are in agreement with the few results currently available in the literature, including the work of (Chakchouk-Mtibaa et al, 2017), where the effect of the semi purified bacteriocin BacFL31 was investigated on the shelf life of refrigerated raw ground turkey meat. The findings indicated that BacFL31 treatments were effective against Listeria monocytogenes and Salmonella Typhimurium.…”
Section: Comparison Of Preservative Potential Of Bacteriocin With Chesupporting
confidence: 92%
“…Recent research indicated that LAB and their natural products can offer promising opportunities for the development of efficient food bio preservation strategies [ 8 , 9 , 10 ]. The potential applications of bacteriocins from LAB as bio-preservatives for the inhibition of proliferation of L. monocytogenes in foods have been reported [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst others, the use of essentials oils, plant extracts or bacteriocins from lactic acid bacteria (LAB) constitute different ways to control lipid and protein oxidation and pathogenic bacteria proliferation in meat systems [3, 1315]. In this context, natural antioxidants from plant extracts have been obtained from different sources such as fruits: grapes, pomegranate, date, kinnow, vegetables: broccoli, potato, drumstick, pumpkin, curry, nettle, herbs and spices, and investigated to decrease lipid oxidation and to preserve and improve the overall quality of meat and meat products [2, 11, 16].…”
Section: Introductionmentioning
confidence: 99%